An Assessment of Regional Bureaucratic Capacity in Implementing Inclusive Economic Development Policies - Syafarddin Syafarddin (International Journal of Economics and Management Research, 2025)
This study evaluates the capacity of regional bureaucracy in implementing inclusive economic development policies in Indonesia. Through an evaluative-qualitative approach, the research examines four dimensions of bureaucratic capacity: institutional, human resources, operational-procedural, and relational-coordinative in case studies across three regions with different typologies. The research findings indicate significant gaps between the required bureaucratic capacity and the actual capacity in the field. Relational-coordinative capacity emerges as a critical factor determining the success of inclusive economic policy implementation, supported by adaptive leadership and collaborative approaches. The study recommends institutional reforms emphasizing collaborative capacity development, decentralized decision-making, and enhanced inclusive economic literacy among the bureaucracy. These findings contribute to the bureaucratic capacity literature by identifying interconnections between capacity dimensions in the context of inclusive economic policy implementation.